Understanding short-term organic matter fluctuations to optimize drinking water treatment. Issue 10 (6th October 2022) - Klante, Clemens; Hägg, Kristofer; Larson, Magnus
Abstract: Increases in organic content and the resulting browning of freshwater are a current and growing challenge for the ecology of these waters, leading to the need for more efforts in drinking water production. This study investigated the implications of short-term changes in the water quality from Lake Bolmen on the treatment process at the downstream located at the Ringsjö water treatment plant. The main objective was to understand short-term organic matter fluctuations to efficiently manage drinking water treatment. The ability to make predictions about expected raw water quality based on variations in the watershed and upstream waters facilitates optimal adjustment of drinking water treatment processes. Key elements in the water supply system studied included a tunnel and pipeline system and a sub-basin of Lake Bolmen. A wealth of data were available for the analysis to establish temporal and spatial properties of the water quality in the system and its dependence on the governing factors. The main factors controlling water quality were identified, both regarding the transport in the tunnel and through the sub-basin, including surface runoff, hydrodynamic properties, sedimentation, resuspension, and biomass availability. Although a particular case was investigated, the study has implications for improving drinking water treatment. HIGHLIGHTS: Analysis of unique long-term hourly data set on water quality in a lake and drinking water system. Coupling of short-term organic matter fluctuations and catchment processes. Influence of wind induced waves on the water color and organic mater content. Graphical Abstract